Geraniol-a potential alternative to antibiotics for bovine mastitis treatment without disturbing the host microbial community or causing drug residues and resistance - Guo, Wei; Qiu, Min; Pu, Zhonghui; Long, Nana; Yang, Min; Ren, Ke; Ning, Ruihong; Zhang, Siyuan; Peng, Fu; Sun, Fenghui; Dai, Min (Frontiers in Cellular and Infection Microbiology, 2023)
Mastitis is one of the most prevalent diseases of dairy cows. Currently, mastitis treatment in dairy cows is mainly based on antibiotics. However, the use of antibiotics causes adverse effects, including drug resistance, drug residues, host-microbiome destruction, and environmental pollution. The present study sought to investigate the potentiality of geraniol as an alternative to antibiotics for bovine mastitis treatment in dairy cows. Additionally, the effectiveness of treatment, improvement in inflammatory factors, the influence on microbiome, presence of drug residues, and drug resistance induction were compared and analyzed comprehensively.Geraniol showed an equivalent therapeutic rate as antibiotics in the mouse infection model and cows with mastitis. Moreover, geraniol significantly inhibited the pathogenic bacteria and restored the microbial community while increasing the abundance of probiotics in milk. Notably, geraniol did not destroy the gut microbial communities in cows and mice, whereas antibiotics significantly reduced the diversity and destroyed the gut microbial community structure. Additionally, no geraniol residue was detected in milk four days after treatment discontinuation, but, antibiotic residues were detected in milk at the 7th day after drug withdrawal. In vitro experiments revealed that geraniol did not induce drug resistance in the Escherichia coli strain ATCC25922 and Staphylococcus aureus strain ATCC25923 after 150 generations of culturing, while antibiotics induced resistance after 10 generations. These results suggest that geraniol has antibacterial and anti-inflammatory effects similar to antibiotics without affecting the host-microbial community structure or causing drug residues and resistance. Therefore, geraniol can be a potential substitute for antibiotics to treat mastitis or other infectious diseases and be widely used in the dairy industry.